ANALISIS KIMIA 9 JENIS KAYU INDONESIA - Gustan Pari; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1990)
This  paper  deals  with  a chemical  analyses  of  nine   species  of  wood  obtained  from industrial plantation forest. The analyses comprised of the determination of  holocellulose, cellulose, lignin, pentosan, moisture content,   ash content, silica  content and  the  solubility in cold  water,   hot  water,  one percent of  sodium   hydroxide   and  ethanol  benzene   (1:2) extractives.The result shows that  holocellulose content ranges  from 57,80 - 66,34 percent,    cellulose  content from 42,23 - 54,91 percent, lignin  from  23,75 - 32,42 percent,  pentosan from 10,10 -19,23 percent, moisture  content  from  10,19 - 26,37  percent, ash content   from   0,25 - 3,08  percent, silica content   from 0,07 - 2,47 percent, solubility in cold  water ranges  from  0,11 - 7,20 percent, solubility in hot  water   from  2,62  -  9,25 percent, solubility in 1%  NaOH from 10,72-19,65  percent   and ethanol  benzene  ranges from  2,09  -  6,13 percent.